Connecting through space and time: catchment‐scale distributions of bacteria in soil, stream water and sediment. (1st October 2019) - Hermans, Syrie M.; Buckley, Hannah L.; Case, Bradley S.; Lear, Gavin
Summary: Terrestrial and aquatic environments are linked through hydrological networks that transport abiotic components from upslope environments into aquatic ecosystems. However, our understanding of how bacteria are transported through these same networks is limited. Here, we applied 16S rRNA gene sequencing to over 500 soil, stream water and stream sediment samples collected within a native forest catchment to determine the extent to which bacterial communities in these habitats are connected. We provide evidence that while the bacterial communities in each habitat were significantly distinct from one another (PERMANOVA pairwise P < 0.001), the bacterial communities in soil and stream samples were weakly connected to each other when stream sediment sample locations were downhill of surface runoff flow paths. This pattern decreased with increasing distance between the soil and sediment samples. The connectivity between soil and stream water samples was less apparent and extremely transient; the greatest similarity between bacterial communities in soil and stream water overall was when comparing stream samples collected 1 week post soil sampling. This study shows how bacterial communities in soil, stream water and stream sediments are connected at small spatial scales and provides rare insights into the temporal dynamics of terrestrial and aquatic bacterial community connectivity.